EMANSIPASI WANITA DI DUNIA ISLAM (Menyoroti Pemikiran Emansipasi Qasim Amin dan Pengaruhnya di Mesir) - Fauziah, Syarifah (An - Nisa`, 2011)
Islam as knowledges the existence of gender-equitable education, because basically in Islam, knowledge is sacred and the search for or demanded is the right and obligation for anyone (male and female) without a difference. Qasim Amin was one af the concerns in the world of thought and renewal of Islam. through the concept of emancipation he stressed the need for women to obtain an education equal to men. It is based on historistas development of Islam it self which does not deny the role of women from time to time. Through the concept of emancipation of his woman about the inportance of woman getting adeguate education, the review of the hijab and the institution of family. He tried to rift the dignity of woman even got the negatif reaktion in his time. But the benefits be felt until now.In the field of education he said the women left behind in education is lagging the nation of progress, this is because the population of a country of approximately 50% are women and how stupid women call educate their children. This means that the progress of a nation lies in the level of education af its citizens, especially women because women are a lot of play to educote, train and shape the character of children who are future leaders of a nation.